Philosophical Perspectives in 21st century education: Globalization, Governance and Post-politics - Magallanes Payan, José Arturo (Disertaciones, 2023)
The purpose of this work is to identify and describe the discursive-hegemonic influences on the contemporary educational phenomenon, its synchronies and dissonances. The analysis of this was based on the perspectives that various authors offer on the exercise of philosophy, mainly the one presented by Alain Badiou of Philosophical Suture, this to synthesize the interweaving between science and politics and show how they constitute their organization of subjectivities and practices within the teaching-learning process. These imbrications and how concepts (skills, effectiveness, success), sutures (post-political technocracy) and trends (sociotechnical paradigm and digital culture) are articulated are exposed as a way to explain and describe how they influence current educational logic. Finally, a possible trend is marked that the analysis of these elements offered, an instructive pedagogy, where the successful operation of the information is the determining factor.